ANALISIS PENGARUH KINERJA KEUANGAN DAN ECONOMIC VALUE ADDED TERHADAP RETURN SAHAM - Ningsih, Susi Mujia; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine and to analyze the influence of financial performance to the stock return of transportation service companies which are listed in Indonesia Stock Exchange in 2011- 2013 periods. The independent variables are Return On Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER) dan Economic Value Added (EVA) to the dependent variable i.e. Stock Return. The research sample has been done by using purposive sampling technique to the 18 companies which have been published their financial statement in 2011- 2013 periods, and 54 financial statements have been met the sample criteria. The data analysis technique has been done by using multiple linear regressions analysis. The result of the research shows that Return on Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER) dan Economic Value Added (EVA) variables have influence to the stock return of transportation service companies which are listed in Indonesia Stock Exchange. Meanwhile, Return on Asset (ROA) does not have any influence to the stock return of transportation service companies which are listed in Indonesia Stock Exchange. And the multiple linear regressions model in this research has the value of R2 is 35.1% which means that 35.1% of stock return can be explained by using Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER) and Economic Value Added (EVA) variables whereas the remaining 64.9% is influenced by other variables outside the model which has been studied.Keywords: Return on Assets, Return on Equity, Earning Per Share, Price Earning Ratio, Economic Value Added, Stock Return.